The bayesian approach of factors associated with preterm birth among mothers delivered at public hospitals in Southeast Ethiopia - Negesse, Yilkal; Abebe, Gossa Fetene (Frontiers in Public Health, 2023)
Background Preterm birth remains the commonest cause of neonatal mortality, and morbidity represents one of the principal targets of neonatal healthcare. Ethiopia is one of the countries which accounts for the highest burden of preterm birth. Therefore, this study aimed to assess factors associated with preterm birth at public hospitals in Sidama regional state. Methods A facility-based cross-sectional study was conducted at public hospitals in Southeast Ethiopia from 1 June to 1 September 2020. To recruit the study participants, systematic random sampling techniques were used. Data were collected using pretested structured interviewer-administered questionnaire and a checklist via chart review. Data were entered using EpiData version 3.1 and exported to R software version 4.0 for analysis. Then, factors associated with preterm birth among mothers were assessed based on the Bayesian statistical approach. Results The study showed that the prevalence of preterm birth was 20.6%. Being a rural resident (AOR = 2; 95% CrI: 1.2–3.5), having no antenatal care service utilization (AOR = 2.3; 95% CrI: 1.1–4.8), hypertensive disorder of pregnancy (AOR = 3.5; 95% CrI: 1.8–6.9), birth space less than 2 years (AOR = 3.4; 95% CrI: 1.5–7.9), having premature rupture of membrane (AOR = 2.4; 95% CrI: 1.3–5.4), and physical intimate violence (AOR = 2.876; 95%CI: 1.534, 5.393) were risk factors of preterm birth. Whereas, women who had primary, secondary, and higher education levels (AOR = 0.2; 95% CrI: 0.1–0.4, AOR = 0.1; 95% CrI: 0.06–0.3, and AOR = 0.2; 95% CrI: 0.1–0.4), respectively, were preventive factors. Conclusion Most of the risk factors of preterm birth were found to be modifiable. Community mobilization on physical violence during pregnancy and antenatal care follow-up are the ground for the prevention of preterm birth because attentive and critical antenatal care screening practices could early identify risk factors. In addition, information communication education about preterm birth prevention was recommended.